Potential of using kaolin as a natural adsorbent for the removal of pollutants from tannery wastewater - Mustapha, S. (Heliyon, 2019)
In the present work, kaolin sample from Gbako Local Government, Niger State, Nigeria was used as an adsorbent for the removal chloride, COD, BOD, sulphate, chromium, cadmium, zinc and the reduction of total alkalinity in tannery wastewater. The kaolin sample was pretreated to enhance its adsorption capacity and then characterized using X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), High Resolution Electron Microscopy (HRSEM), High Resolution Transmission Electron Microscopy (HRTEM), Energy Dispersive Spectroscopy (EDX), Selective Area Electron Diffraction (SAED) and Brunauer Emmett-Teller (BET). The specific surface area, pore volume and pore diameter of the kaolin were 17 m(2)/g, 0.018 cm(3)/g and 3.587 nm, respectively. The adsorption methods of the parameters onto the kaolin were investigated as functions of contact time, adsorbent dosage and temperature. Equilibrium isotherms for the adsorption parameters were carried out experimentally and the adsorption data correlated very well with Jovanovic and Redlich-Peterson models. Furthermore, the adsorption kinetics followed the Avrami model. From the results of the study it was established that kaolin from Gbako, Nigeria can serve as an economic, safe and effective natural adsorbent for the pollutants removal from tannery wastewater.